Chronic total occlusion techniques in non-chronic total occlusion cases, the wealth of a large toolbox. Issue 6 (3rd September 2021) - Wilgenhof, Adriaan; Zivelonghi, Carlo; Budassi, Simone; Agostoni, Pierfrancesco; Scott, Benjamin
Abstract: The development of dedicated expertise in chronic total occlusion (CTO) percutaneous coronary interventions (PCI) techniques is a time-consuming process that makes the CTO-operator more versatile and resolute in routine PCI. We describe three characteristic cases where the use of a specific CTO-technique was applied in the setting of complicated PCI to prevent a "nightmare" in the catheterisation laboratory. More specifically, management of occlusive dissections was successfully mastered with a retrograde technique in the first case, with a sub-intimal transcatheter withdrawal technique in the second one and with an antegrade dissection-re-entry technique in the last patient. In all the described cases, the adoption of these advanced techniques would have been substantially unfeasible for non-CTO operators or without a CTO-operator guidance. Fellows undergoing training in invasive cardiology should be encouraged to enrol in a CTO programme for at least part of their fellowship in order to become acquainted to these CTO techniques.